Improving Patient-Assessed Outcomes after Cataract Surgery. Issue 4 (26th June 2017) - Samadi, Behrad; Lundström, Mats; Kugelberg, Maria
Purpose: To identify and evaluate possible causes of poor patient-reported visual function after cataract surgery. Methods: We obtained retrospective data from the Swedish National Cataract Register on patient self-assessed visual function before and after cataract surgery based on the Catquest-9SF questionnaire. We identified patients who self-reported similar or more difficulties postoperatively than preoperatively, and looked at possible causative variables such as sex, age, preoperative and postoperative corrected distance visual acuity (CDVA) and refractive errors, and ocular comorbidity. Results: Nearly 75% of the 119 patients identified had a better postoperative CDVA; the mean CDVA increased by over 0.2 logarithm of the minimum angle of resolution visual acuity. Patients with low or high preoperative CDVA had poor self-assessed outcomes postoperatively. Younger patients (52-68 years) had a lower self-assessed outcome than more elderly patients. Surgical complications and poor near vision yielded lower outcomes. Anisometropia, ocular comorbidity, and sex did not significantly affect the outcome in this specific group. Conclusions: Patients content with their visual function despite the presence of a cataract should defer surgery. This may also include patients younger than 68 years with good visual function. Detailed information given to the patients about their ophthalmic condition, the surgical procedure and risks, and the eventual need for reading glasses postoperatively may result in higher self-assessed visual function outcomes among patients.